RO reject water characteristics, environmental impacts and management - Vaishnav, Jyoti; Jaina, Pankaj Kumar; Soloman, Prama Esther; Lal, Chhagan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Supply of potable water to every citizen is the prime challenge to many countries. Water purification is done by so many methods but reverse osmosis (RO) process using membrane is extensively used throughout the world. This technology is widely applied to meet potable water quality standard. In this process ground or surface water is used as feed water and pure water and Reverse Osmosis Concentrate (ROC) are formed as product and by product respectively. ROC is discharged in this reverse osmosis process and it contains dissolved inorganic and organic pollutants. RO system permits the separation of water molecules and salts through a semi-permeable membrane by pressure gradient. In household, reverse osmosis unit uses a lot of water as a feed water due to low back pressure system, as a result recovery is less and a lot of water go as waste, which has no further use. RO process discharge water is almost 50% of feed water and it is one of the major drawbacks of this process. The concentration of contaminants in RO reject is influenced by the nature of feed water as well as the kind of membrane being used in RO system along with applied pressure and recovery rate of the system. RO brine is a significant component of desalination plant because there are management issues related to its proper treatment and disposal of the ROC is an important part of sustainable water treatment practice. RO waste water may have catastrophic consequences for water stressed regions and mega cities and it is the biggest task in present time. This review highlights the RO process and reverse osmosis concentrate or rejected water together with their physicochemical parameters, potential risk by using RO concentrate disposal methods and environmental benefits of reusing brine water which can resolve the problem of water scarcity. The study revealed that RO waste water disposal problem can be minimized by reclaiming the RO brine and using it for fish farming, irrigation, producing salt and in brick formation. Hence this manuscript proposes an environmentally friendly approach for sustainable management of RO brine water.